(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
This paper attempts to answer the question whether transparent and timely preparation of the Public Debt Management Strategy of the Republic of Croatia can improve the quality of management of public debt in Croatia, and with that, if it can affect the quality of budget policy in general. The terms public debt management and debt management strategy are not new in the professional and scientific literature. Certain suggestions and solutions already exist, but failed to be implemented. Deadlines for the preparation, as well as the content of the public debt management strategy, are not legally regulated. As a result, only two strategies have been prepared so far, and only one has met the defined standards. Furthermore, PDMS[i] for the current period does not exist, and it is questionable by which guidelines public debt management in Croatia has been carried out. The paper is composed of two parts. The first part shows the theoretical overview and analysis of the current state of public debt in the Republic of Croatia. The second part deals with the theoretical guidelines and quality analysis of previous versions of PDMS. Keywords: Public debt, management of public debt, Public Debt Management Strategy of the Republic of Croatia [i] Public Debt Management Strategy (hereinafter PDMS)